2018
DOI: 10.1111/jir.12475
|View full text |Cite
|
Sign up to set email alerts
|

Embedding routine health checks for adults with intellectual disabilities in primary care: practice nurse perceptions

Abstract: While the trial found the intervention to be dominant over standard health care, the adjustments nurses made may not have maximised potential benefits to patients. Increasing training could further improve the benefits that health checks provide for people with IDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(29 citation statements)
references
References 25 publications
0
29
0
Order By: Relevance
“…These comprehensive health assessments, conducted as preventive and diagnostic measures, in primary‐care clinics have been shown to be beneficial for health of people with DDs. The health checks for one patient with DDs typically took 48 min to carry out (Macdonald et al, 2018). The time required to administer the health check was centred around the operational impact on how this intervention impinged on nurses' everyday workload and practice particularly if dealing with larger numbers of patients (Macdonald et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…These comprehensive health assessments, conducted as preventive and diagnostic measures, in primary‐care clinics have been shown to be beneficial for health of people with DDs. The health checks for one patient with DDs typically took 48 min to carry out (Macdonald et al, 2018). The time required to administer the health check was centred around the operational impact on how this intervention impinged on nurses' everyday workload and practice particularly if dealing with larger numbers of patients (Macdonald et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…The health checks for one patient with DDs typically took 48 min to carry out (Macdonald et al, 2018). The time required to administer the health check was centred around the operational impact on how this intervention impinged on nurses' everyday workload and practice particularly if dealing with larger numbers of patients (Macdonald et al, 2018). Ndengeyingoma and Ruel (2016) identified that nurses had insufficient time to intervene adequately in situations concerning people with DDs in the emergency room and hospital ward, particularly when care was urgent.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations